2018
DOI: 10.1101/lm.046284.117
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dietary creatine enhances hippocampal-dependent spatial memory, bioenergetics, and levels of plasticity-related proteins associated with NF-κB

Abstract: The brain has a high demand for energy, of which creatine (Cr) is an important regulator. Studies document neurocognitive benefits of oral Cr in mammals, yet little is known regarding their physiological basis. This study investigated the effects of Cr supplementation (3%, w/w) on hippocampal function in male C57BL/6 mice, including spatial learning and memory in the Morris water maze and oxygen consumption rates from isolated mitochondria in real time. Levels of transcription factors and related proteins (CRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 93 publications
(106 reference statements)
4
26
3
Order By: Relevance
“…These findings also have important implications for AD treatment as demonstrated by recent studies by Snow et al (2018) and as shown in other related studies (Djordjevic et al, 2017; Adlimoghaddam et al, 2019) that suggest targeting NF-κB signaling in the mitochondria may have therapeutic value. For example, in Snow et al’s study, creatine – a known modulator of mitochondrial function (Tarnopolsky and Beal, 2001), was shown to increase and positively alter protein levels of CaMKII, PSD-95, and Complex 1 subunits in creatine fed mice, whereas the NF-κB inhibitory IκB subunit was decreased.…”
Section: Nf-κb Mediates Aβ-induced Dysfunction In the Mitochondriasupporting
confidence: 68%
“…These findings also have important implications for AD treatment as demonstrated by recent studies by Snow et al (2018) and as shown in other related studies (Djordjevic et al, 2017; Adlimoghaddam et al, 2019) that suggest targeting NF-κB signaling in the mitochondria may have therapeutic value. For example, in Snow et al’s study, creatine – a known modulator of mitochondrial function (Tarnopolsky and Beal, 2001), was shown to increase and positively alter protein levels of CaMKII, PSD-95, and Complex 1 subunits in creatine fed mice, whereas the NF-κB inhibitory IκB subunit was decreased.…”
Section: Nf-κb Mediates Aβ-induced Dysfunction In the Mitochondriasupporting
confidence: 68%
“…In vitro, the neuroprotective effects of Cr appear to be mediated by NF-κB-dependent pathways, as treatment of cultured neurons with Cr reduced levels of IκB, the NF-κB tethering protein, consistent with enhanced activation of NF-κB with Cr [ 18 ]. Consistent with such data, our previous work with Cr supplementation in C57BL/6 mouse model [ 19 ] demonstrated a similar reduction in hippocampal IκB protein levels, consistent with increased activation of NF-κB, as well as elevations in calcium-calmodulin-dependent protein kinase II (CaMKII), a protein shown to be required for long-term memory formation [ 20 ] and for which isoforms serve as both activators [ 21 ] and downstream targets of NF-κB [ 22 ]. Further, hippocampal levels of postsynaptic density protein 95 (PSD-95), a synaptic protein implicated in learning and memory that is also under the transcription regulation of neuronal NF-κB [ 23 ], were increased in Cr-supplemented mice.…”
Section: Introductionsupporting
confidence: 87%
“…Further, hippocampal levels of postsynaptic density protein 95 (PSD-95), a synaptic protein implicated in learning and memory that is also under the transcription regulation of neuronal NF-κB [ 23 ], were increased in Cr-supplemented mice. Importantly, these molecular alterations were accompanied by enhanced hippocampal-associated learning, memory, and mitochondrial function [ 19 ]. Moreover, a subunit of complex I of the electron transport chain, which is intricately involved in mitochondrial function, was elevated with oral Cr [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, creatine may support cognitive function during stress in human [53] and animal studies [20,21]. However, it is not clear whether this increased support was due to enhanced anaerobic demands in brain, as chronically supplemented mice had enhanced in vitro oxidative phosphorylation in hippocampal mitochondria [9]. Further studies might investigate the ontogeny of brain creatine metabolism in vivo in the more translational pig model.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in rats show improved efficiency with spatial working memory during chronic stress following a single creatine dose [8]. Whereas mice chronically supplemented with creatine elicited better performance on a variety of memory tasks and had improved mitochondrial energetics [9]. Many have argued that creatine has neuroprotective effects that may be beneficial after mild brain trauma [10], or in neurodegenerative disease [11].…”
Section: Introductionmentioning
confidence: 99%